Menggagas Laporan Keuangan Syari’ah Berbasis Trilogi Ma’isyah-Rizq-Maal - Aji Dedi Mulawarman (Institute for Research and Community Empowerment (LPPM TAZKIA), 2009)
The objective of this research to formulate Shari’ate Financial Statements from the real transaction and business habitus of Indonesian Moslem Society. Formulation is conducted by utilising Two-Steps Tazkiyah Methodology. Step one in that methodology, conventional concept of financial statements and Baydoun and Willett’s (1994) Islamic Corporate Report’s are refined by Shari’ate Accounting (derived from Islamic Values and Maqashid Asy- Syari’ah). Step two, the result is then refined by (Islamic) Technosystem and Constructivist Structuralism to generate Shari’ate Financial Statements. The first result shows that ma’isyah-rizq-maal trilogy are the substance’s of shari’ate financial statements. Ma’isyah is a representation of Islamic business transaction. Rizq is a representation of Islamic value added creation. Maal is a representation of Islamic wealth. The consequence of the first results shows that formulation of: (1) shari’ate cash flow statement is based on ma’isyah concept; (2) shari’ate value added statements is based on rizq concept; and (3) shari’ate balance sheet is based on maal concept.Keywords: Maisyah-Rizq-Maal Trilogy, Shari’ate Financial Statements, Shari’ate Cash Flow